Reporting as a property and genre of tv journalism - Zagrebelnaya, C. (ХНУ ім. В. Н. Каразіна, 2012)
The article deals with TV reporting. Mass media is considered as one of the most characteristic features of modern civilization. Mass media is classified into newspapers, magazines, radio, and TV. Reporting is considered as a very important property of television. The conclusion is made that TV reporting is a unique genre which requires knowledge, experience and great responsibility.
Статья посвящена телевизионному репортажу. Средства массовой информации – одна из самых характерных черт современной цивилизации. Средства массовой информации делятся на газеты, журналы, радио и телевидение. Репортаж рассматривается как очень важное свойство телевидения. Делая вывод, можно сказать, что телевизионный репортаж – уникальный жанр, который требует знаний, опыта и большой ответственности
Keywords: mass media; Television reporting; magazine; newspaper; radio